2007
DOI: 10.1111/j.1600-0870.2006.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Decadal variations in mean and extreme sea level values along the Estonian coast of the Baltic Sea

Abstract: This study presents an overview of the Estonian sea level data set obtained from the coastal tide gauges over the period 1842–2005. Variations in the time‐series of annual mean sea level, maxima and minima, as well as standard deviations are investigated and their relationships with variations in the North Atlantic Oscillation index are studied. After correcting the sea level series to spatially varying land uplift rates the series display increasing (1.5–2.7 mm yr−1) trends, which in case of Pärnu tide gauge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 46 publications
(83 reference statements)
3
54
0
Order By: Relevance
“…Studies at the Estonian coastline showed a remarkable rise in annual sea level maxima of 3.5-11 mm year −1 after correcting for local uplift rates (Vallner et al 1988;Suursaar and Sooäär 2007). Even excluding the prominent event of 2005, the rise in annual sea level maxima was significantly higher than the rise in MSL (1-2.6 mm year −1 ) and the rise in annual sea level minima (0.8-3.1 mm year −1 ).…”
Section: Statistics and Long-term Trendsmentioning
confidence: 95%
See 2 more Smart Citations
“…Studies at the Estonian coastline showed a remarkable rise in annual sea level maxima of 3.5-11 mm year −1 after correcting for local uplift rates (Vallner et al 1988;Suursaar and Sooäär 2007). Even excluding the prominent event of 2005, the rise in annual sea level maxima was significantly higher than the rise in MSL (1-2.6 mm year −1 ) and the rise in annual sea level minima (0.8-3.1 mm year −1 ).…”
Section: Statistics and Long-term Trendsmentioning
confidence: 95%
“…The correlation between the NAO and Baltic Sea sea level is especially strong in winter (e.g. Andersson 2002;Dailidienė et al 2006;Hünicke and Zorita 2006;Suursaar and Sooäär 2007), and in northern and eastern parts of the Baltic Sea Suursaar et al 2006a) (see Fig. 9.4, right panel).…”
Section: Meteorological Influencementioning
confidence: 99%
See 1 more Smart Citation
“…The plots of empirical return periods against the corresponding theoretical (e.g. Gumbel) distributions [Suursaar and Sooäär, 2007] showed a more or less a satisfactory fit in all cases except Pärnu maxima. No extreme value distributions could probably describe or predict the two extreme sea level events of 253 cm or 275 cm (Fig.…”
Section: Analysis Of Extremes -A Tool For Coastal Managementmentioning
confidence: 99%
“…According to the data published by Bogdanov et al [2000], the mean was 5.9 cm in 1971-1993. Instead, the mean sea level of Estonian tide gauges is roughly around the Kronstadt zero now [Suursaar and Sooäär, 2007].…”
Section: Fig 2 Time Series Of Mean and Extreme Sea Level Available mentioning
confidence: 99%